Disabled person: construction of concept by this population - Lorita Marlena Freitag Pagliuca; Paula Marciana Pinheiro de Oliveira; Monaliza Ribeiro Mariano; Jacqueline Mota da Silva; Paulo Cesar de Almeida; Giselly Oseni Barbosa Oliveira (Universidade Federal do Ceará, 2015)
Objective: to build the concept of disabled person. Methods: study of analysis of concept using the phases field work andstatistical analysis with 120 individuals divided into three groups of 40 people with hearing, visual and motor disability.Results: there was predomination of men (68%), 18-29 years old (55%), with superior education (35%) and married/common-law married (75%). The attribute accepted was person with limitation and still able to perform activity, witha difference between groups (p = 0.018); the keyword accepted was limitation (p = 0.001); the expression was disabledperson, with intergroup difference (p = 0.013). Concept of choice by group was deaf (97.51%); blind (45%) and person withvisual disability (45%) and; person with physical disability (27.5%). Conclusion: attributes, keywords used in the literatureand public policy were not accepted. They prefer to be called deaf; blind or visually impaired; They reject people with motordisability and wheelchair user.